1990
DOI: 10.1177/154193129003401726
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Driving Simulation Facility for Instrument Panel Task Performance

Abstract: The purpose of this study was to compare driver performance of 17 conventional automotive instrument panel (IP) tasks on the road and in the driving simulator and to validate use of the simulator in evaluation of an IP design. Introduction of random crosswind was shown to influence the driving workload in the simulator. Comparisons of the visual attentional and manual demand measures demonstrated that a driving environment close to that in the car is provided by the simulator at zero crosswind level and that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 1 publication
3
7
0
Order By: Relevance
“…Time pressure and forward scene uncertainty build to the point that the driver is compelled to return glance to the forward scene. and Kurokawa and Wierwille (1990) have found that drivers behave as might be expected from the model presented in Section 1.0 of this report:…”
Section: -10supporting
confidence: 63%
See 1 more Smart Citation
“…Time pressure and forward scene uncertainty build to the point that the driver is compelled to return glance to the forward scene. and Kurokawa and Wierwille (1990) have found that drivers behave as might be expected from the model presented in Section 1.0 of this report:…”
Section: -10supporting
confidence: 63%
“…For in-vehicle tasks, most of which are performed on straight or only slightly curved sections of road, the driver can ordinarily make a hand available for in-cab device use. Hand-off-wheel time has been measured in at least two studies (Kurokawa and Wierwille, 1990;Hayes, Kurokawa, and Wierwille, 1989). Their results show that, for conventional tasks, mean hand-off-wheel time ranges from about 1.25 seconds (press one of three buttons on a radio) to about 12.5 seconds (press AM/FM, then tune to a specific frequency using a digital dial and rate change tuning control).…”
Section: -12mentioning
confidence: 99%
“…Early eye glance research focused on driving alone and indicated that, as experienced drivers became familiar with a route, they were better able to detect potential traffic threats due to a strategy of confining their visual zone and of looking straight ahead (9,10). Other research studied the eye glance patterns of drivers as they performed secondary tasks (e.g., radio, speedometer, navigation systems) (11)(12)(13)(14), including measures such as visual glance duration, number of glances per task, glance frequency (glances to a particular target), glance duration (including transition movement), percentage of time (at a target), number of glances during a task, eyes-off-road (EOR) time, and task completion time (e.g., 15,16), following standardized methods (17). Recent driving research on experienced drivers revealed that, during driving while engaged in no other tasks, the instrument panel received almost twice as many glances as the left mirror, which in turn received more than twice as many glances as the rearview mirror (RVM).…”
Section: Background Eye Glance Research Relevant To Experienced Driversmentioning
confidence: 99%
“…Measures of eye movements have been investigated in terms of the number of eye glances, total glance time, mean glance time to a particular location, total eyes-off-road time, and total task time (the time to complete a task). For example, driving research has been conducted on the performance of completing in-vehicle tasks such as adjusting the radio, viewing in-vehicle displays (e.g., speedometer) or interacting with a navigation system Gellatly & Kleiss, 2000;Kurokawa & Wierwille, 1990;Tijerina, Palmer & Goodman, 1999). Visual glance duration and the number of glances per task were investigated while performing conventional in-vehicle tasks and navigation tasks .…”
Section: Eye Movementsmentioning
confidence: 99%